RecA protein stimulates homologous recombination in plants. - Reiss, B (1996)
A number of RecA-like proteins have been found in eukaryotic organisms. We demonstrate that the prokaryotic recombination protein RecA itself is capable of interacting with genomic homologous DNA in somatic plant cells. Resistance to the DNA crosslinking agent mitomycin C requires homologous recombination as well as excision repair activity. Tobacco protoplasts expressing a nucleus-targeted RecA protein were at least three times as efficient as wild-type cells in repairing mitomycin C-induced damage. Moreover, homologous recombination at a defined locus carrying an endogenous nuclear marker gene was stimulated at least 10-fold in transgenic plant cells expressing nucleus-targeted RecA. The increase in resistance to mitomycin C and the stimulation of intrachromosomal recombination demonstrate that Escherichia coli RecA protein is functional in genomic homologous recombination in plants, especially when targeted to the plant nucleus.